2018
DOI: 10.1093/gji/ggy520
|View full text |Cite
|
Sign up to set email alerts
|

Assessing middle atmosphere weather models using infrasound detections from microbaroms

Abstract: SUMMARY The nonlinear interaction of ocean surface waves produces coherent infrasound noise—microbaroms—between 0.1 and 0.5 Hz. Microbaroms propagate through the atmosphere over thousands of kilometres due to low absorption and efficient ducting between the ground and the stratopause. These signals are globally and permanently detected by the International Monitoring System (IMS) infrasound network, which has been established to monitor compliance with the Comprehensive Nuclear-Test-Ban Treaty. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…Atmospheric specifications are given at the station and are assumed to be constant along the propagation path. This approach shows good results for microbaroms generated in the northern hemisphere similar to those described by De Carlo et al 2018and Hupe et al (2018). However, such an approach does not explain the observed microbarom amplitude for sources located south of the stations.…”
Section: Source Modellingsupporting
confidence: 69%
See 2 more Smart Citations
“…Atmospheric specifications are given at the station and are assumed to be constant along the propagation path. This approach shows good results for microbaroms generated in the northern hemisphere similar to those described by De Carlo et al 2018and Hupe et al (2018). However, such an approach does not explain the observed microbarom amplitude for sources located south of the stations.…”
Section: Source Modellingsupporting
confidence: 69%
“…Where previous studies analysed microbarom signals at a single station (Hupe et al, 2018), further investigations are conducted in this study by considering a multi-year dataset of continuous records collected by the IGR network. Regional features of both microbaroms and microseisms are highlighted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…well as for long-term assessment of model product uncertainties, particularly when applied to data from a global network of infrasound stations. A key aspect of this approach is that benchmarking between model and infrasound vespagrams considers all back-azimuth directions rather than just the direction of the dominant microbarom source, as done in several previous studies (Garcés et al, 2004;Hupe et al, 2019;De Carlo et al, 2019;Smirnov et al, 2020;De Carlo et al, 2020). The microbarom soundscape at a station is typically a sum of components stemming from a wide spatial distribution of ocean regions, and recently den Ouden et al (2020) demonstrated that an iterative decomposition of the array spatial covariance matrix using the CLEAN algorithm (Högbom, 1974) can be exploited to resolve the back-azimuth and trace velocity of the most coherent wave front arrivals.…”
Section: 2)mentioning
confidence: 99%
“…In addition to prospective numerical weather prediction improvements, the suggested vespagram-based approach may be applied in multi-technology studies of atmospheric dynamics, for example initiatives building on the Atmospheric dynamics Research InfraStructure in Europe (ARISE) projects (Blanc et al, 2018(Blanc et al, , 2019. These aim at harvesting from synergies between ground-based infrasound observations, radar and lidar systems, as well as airglow and satellite observations to monitoring the middle atmosphere (Chunchuzov et al, 2015;Le Pichon et al, 2015;Blanc et al, 2018;Hupe et al, 2019;Smets et al, 2019;Hibbins et al, 2019;Assink et al, 2019; Le Pichon et al, 2019).…”
Section: 2)mentioning
confidence: 99%